2008
DOI: 10.1111/j.1439-0329.2008.00558.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in susceptibility of six pine species and hybrids to pitch canker caused by Fusarium  circinatum

Abstract: Six pine species or hybrids were tested for susceptibility to pitch canker caused by Fusarium circinatum. Pinus densiflora, Pinus thunbergii, Pinus x rigitaeda (Pinus rigida · Pinus taeda), P. rigida · P. x rigitaeda, Pinus echinata and Pinus virginiana were inoculated with three spore loads (50, 500 and 5000 per tree) of F. circinatum. External symptoms, lesion length, and the frequency of reisolation of the fungus were investigated. External symptoms were greatest in P. echinata, followed by P. virginiana, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 13 publications
1
21
0
Order By: Relevance
“…However, native two-needle pine, P. thunbergii, is also being damaged by the disease especially in Jeju Island. In a previous test, we found that the mortality of three-yearold seedlings of P. × rigitaeda inoculated with an isolate from P. rigida in Baekryeong Island, Kyeonggi province, South Korea was zero (Kim et al, 2008). However, in this study, most of the seedlings of P. × rigitaeda had died by the fungus isolated from P. thunbergii.…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…However, native two-needle pine, P. thunbergii, is also being damaged by the disease especially in Jeju Island. In a previous test, we found that the mortality of three-yearold seedlings of P. × rigitaeda inoculated with an isolate from P. rigida in Baekryeong Island, Kyeonggi province, South Korea was zero (Kim et al, 2008). However, in this study, most of the seedlings of P. × rigitaeda had died by the fungus isolated from P. thunbergii.…”
Section: Resultsmentioning
confidence: 61%
“…In the recent study, 2 of 6 pine species or hybrid seedlings, P. echinata and P. virginiana, were the most susceptible to infection by Korean isolate of F. circinatum (Kim et al, 2008). However, some studies provided solid evidence on the seasonal and weather-related variations in levels of spore deposition rates of F. circinatum (Garbelotto et al, 2008;Schweigkofler et al, 2004).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…This finding is consistent with results obtained by Elvira-Recuenco et al [46] and Swett et al [47] who found symptomless P. radiata seedlings for 475 days after inoculation or at least 52 weeks, respectively. Other studies also demonstrated the presence of asymptomatic seedlings, but all of them were conducted on Pinus species [42][43][44]. To our knowledge, this is the first study in which the presence of asymptomatic yet infected seedlings has been recorded in the Picea and Larix genera.…”
Section: Discussionmentioning
confidence: 73%
“…(Kim, Woo, Koo, & Yeo, 2008). Another study found that wounding due to weather events provided the primary infection courts for F. circinatum (Woo, Y.J.…”
Section: Pitch Canker Resistance Trialsmentioning
confidence: 99%